Timeline of the Malay jawi works: a revisit to the oldest known Malay manuscript - Jusoh, Che' Razi; Elias @ Mayah, Aliza (Department of Usuluddin and Comparative Religion, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University of Malaysia, 2018)
The paper examines the dating of writings on Islam originating in the Malay world in the form of either treatise (risālah) or book (kitāb) as there are disagreements on the date of the advent of Islam in the region. The researchers revisit the polemic of the topic of the oldest known Malay manuscript between the ‘Aqā’id al-Nasafī by anonymous author dated 1590 A.D and the Baḥr al-Lāhūt of Shaykh ʿAbdullah ʿArif which was said to have been written in 12th century A.D., is 400 years older than the former. In order to lit light on this issue, the researchers employ the qualitative methodology in which the linguistic, textual and comparative analysis are applied on the manuscripts and material related to both treatises. Finding reveals that there are some methodological issues that need to be resolved in comparing both treatises.